Values of Local Wisdom and Sasirangan Tourism in The City of Banjarmasin, South Kalimantan, Indonesia - Permatasari, Melly Agustina; Astuti, Tri Marhaeni Pudji; Setyowati, Dewi Liesnoor; Abbas, Ersis Warmansyah (Journal of Ecohumanism, 2025)
Sasirangan as a regional cloth for the City of Banjarmasin, South Kalimantan, has various Sasirangan motifs that contain local wisdom values ​​that are believed by the community. The purpose of this research is to analyze the value of local wisdom of Sasirangan and Sasirangan tourism in the city of Banjarmasin, South Kalimantan. This research uses qualitative and quantitative approaches with descriptive methods. The research location is in the city of Banjarmasin, South Kalimantan. The informants of this research are Sasirangan craftsmen. Data collection through observation, interviews, online surveys, and documentation. Research data analysis techniques are thematic, textual, contextual and interpretive.